A P1-based physical map of the Drosophila euchromatic genome. - Kimmerly, W; Stultz, K; Lewis, S; Lewis, K; Lustre, V; Romero, R; Benke, J; Sun, D; Shirley, G; Martin, C; Palazzolo, M (Genome Research, 1996)
A PCR-based sequence-tagged site (STS) content mapping strategy has been used to generate a physical map with 90% coverage of the 120-Mb euchromatic portion of the Drosophila genome. To facilitate map completion, the bulk of the STS markers was chosen in a nonrandom fashion. To ensure that all contigs were localized in relation to each other and the genome, these contig-building procedures were performed in conjunction with a large-scale in situ hybridization analysis of randomly selected clones from a Drosophila genomic library that had been generated in a P1 cloning vector. To date, the map consists of 649 contigs with an STS localized on average every 50 kb. This is the first whole genome that has been mapped based on a library constructed with large inserts in a vector that is maintained in Escherichia coli as a single-copy plasmid.